The awareness level of 21st century skills and its correlation with leadership behaviour for secondary school principals in Baghdad (Journal of the College of Basic Education, 2025)
This study aimed to measure the level of awareness of secondary school principals in Baghdad Governorate of the 21st century skills and its correlation to their leadership behaviour. The researcher used the questionnaire as a main tool for collecting his data. The researcher designed two questionnaires for this study. It has been benefited from the 21st century school leadership skills questionnaire which produced by the National Association of Secondary School Principals (NASSP). The leadership behaviour scale included (21) statements divided into three dimensions (setting instructional direction, teamwork, sensitivity), while the 21st century skills questionnaire included also three dimensions (resolving complex problems, communication, developing self and others) which consisted of (34) statements. The questionnaires were distributed to a sample of (130) male and female principals in secondary schools in Baghdad Governorate. The outcomes indicated a high level of awareness of secondary school principals in the 21st century skills. Further, the vast majority of secondary school principals practice leadership behavior in their schools in a high degree. The results also showed a weak correlation between the degree of awareness of secondary school principals in Baghdad Governorate of the 21st century skills and its leadership behavior. The results also showed statistical differences attributed to gender variable, in favour of females.